Conditions underlying agricultural land lease in Poland, in the context of the agency theory. (March 2021) - Marks-Bielska, Renata
Highlights: In the article presented character of farmland lease in Poland. The lease of agricultural land is an important form of land use in most of the EU. Presented research into the land-owner-lessee relations. It is expedient that a new legal status of agricultural land lease be defined. Abstract: Research into the land owner-lessee relationship is among the oldest and classic examples of analyses made by economists into agency relationships, the fact that has encouraged the author to carry out this empirical study among agricultural land lessees in Poland (227 agricultural producers who lease farmland). The objective was to gain the knowledge of how this form of land use and farmland management was perceived by lessees. The research results were enriched with an analysis of the data from public statistics and an overview of the most important legal acts creating the institutional framework for land use in the form of lease in Poland. The survey addressed to lessees of farmland from the Agricultural Property Stock of the State Treasury confirmed that there is information asymmetry between the principal (the National Support Centre for Agriculture) and the agent (the lessee), including the knowledge of such facts as the application of agronomic treatments on leased land or volumes of harvested yields. What makes the research subject more important is the specific character of farmland lease in Poland, that is a lack of a legal act dedicated strictly to this institution compounded by frequent changes in legal regulations indirectly governing land lease, which both affect the scope and popularity of this form of agricultural land use. The agricultural policy in Poland regarding the institution of lease is inconsistent. The question that needs to be resolved is whether this form of land use in agriculture will be supported and perpetuated, or whether it will be treated as a transient form of land use leading to complete ownership transformation.